New Inscriptions from Northeast Phrygia: The Cult of Hosios and Dikaios - Hale Güney (Gephyra, 2018)
The last three decades have witnessed increasing number of publications on the cult of Hosios kai Dikaios, Holy and Just, a cult predominantly found in Phrygia and Lydia worshipped together with Helios and Apollo. Due to various reasons, this cult, however, is less examined within archaeological context in which votive inscriptions emerged. The lack of archaeological context prevents us to evaluate the origins and organization of the cult under consideration. This paper presents the initial results of an epigraphic survey carried out since 2014 in northeast Phrygia. The first surveyed area today encompassing Mihalıççık County in Eskişehir province is located between the Sakarya (Sangarios) river to the north and the Porsuk (Tembris) river to the south. This paper focuses on two groups of new inscriptions found in Kayı and Otluk villages and their vicinities located in Mihalıççık County. It also includes one inscription (no. 5) which was incompletely published by Anderson. The discovery of four inscriptions offers some new information about the cult of Hosios and Dikaios, possible locations for the sanctuary/shrine of the cult and the provenance of the stone used for votive inscriptions in northeast Phrygia. The paper begins by laying out the historical geography of survey area, and then it presents the inscriptions and commentaries. It finally evaluates the evidence with reference to archaeological context including general historical conclusions.